La memoria de la violencia: las consecuencias del conflicto armado contra Sendero Luminoso representadas en una película y dos novelas peruanas - Sagermann Bustinza, Leonor (Wydawnictwo Naukowe UAM, 2014)
The peculiar situation of violence experienced in Peru of the 1980s and the 1990s shows a society immersed in the trauma, suffering and pain. The literature as well as the film have become a means to reflect the painful experience of the society. The aim of this article is to analyse some of the main characters of the novels: 'La hora azul' (2005) by Alonso Cueto, 'Abril rojo' by Santiago Roncagliolo (2006), and the film: 'La teta asustada' (2009) by Patricia Llosa in order to show the effects of traumatic experiences of the past and an attempt to return to normal life.
The memory of violence: the consequences of a armed war against the Shining Path in a Peruvian film and two Peruvian novels
Keywords: violence; memory; trauma; Shining Path (Sendero Luminoso); Peruvian literature; cinema